Phenytoin-induced bradycardia and hypotension - Mathews, Swetha Reba (Indian J Pharmacol, 2019)
Phenytoin is an anticonvulsant which is also a Class IB antiarrhythmic. Its common adverse drug reactions (ADRs) include gastrointestinal symptoms, psychiatric disorders, gingival hyperplasia, and rash. Bradycardia and hypotension following intravenous (IV) phenytoin are rare ADRs. We report the case of a 62-year-old female with subarachnoid hemorrhage and right bundle branch block, who developed sinus bradycardia and hypotension on administration of IV phenytoin. This case report serves as a note for caution on patient selection for the administration of phenytoin and highlights the need for specific guidelines on the same.